VII INTERNATIONAL CONGRESS DEDICATED TO A. F. SAMOILOV "FUNDAMENTAL AND CLINICAL ELECTROPHYSIOLOGY. CURRENT ISSUES OF MEDICINE". COLLECTION OF ABSTRACTS - article Editorial (Российский кардиологический журнал)
.